2014
DOI: 10.1590/1519-6984.14312
|View full text |Cite
|
Sign up to set email alerts
|

The role of melanism in oncillas on the temporal segregation of nocturnal activity

Abstract: The occurrence of coat colour polymorphisms in populations may promote the ecological success of species by permitting a wider spectrum of use of different subsets of available resources. We conducted an analysis of temporal segregation by comparing night brightness with nocturnal activity of spotted and melanistic oncillas (Leopardus tigrinus). Melanistic oncillas were more active during bright nights and spotted oncillas and other species were more active during dark nights. Each colour morph occupied a temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 22 publications
2
25
2
Order By: Relevance
“…Likewise, statistical comparisons of activity records between two colour morphs of oncilla Leopardus tigrinus revealed significant intraspecific differences in diel activity patterns (Graipel et al. ).…”
Section: Investigating Changes To Species Activity Patterns and Nichementioning
confidence: 99%
“…Likewise, statistical comparisons of activity records between two colour morphs of oncilla Leopardus tigrinus revealed significant intraspecific differences in diel activity patterns (Graipel et al. ).…”
Section: Investigating Changes To Species Activity Patterns and Nichementioning
confidence: 99%
“…Graipel et al. () found that melanistic oncillas were more active during bright nights than spotted oncillas, suggesting that melanistic individuals could occupy an alternative and wider ecological niche than spotted individuals. Similarly, Kawanishi et al.…”
mentioning
confidence: 99%
“…This result is consistent with other studies that have shown that genetically determined melanic body color is associated with variation in aggression and other behaviors. This pattern has been found in fruit flies (Takahashi 2013), other fish (Kittilsen et al 2009), reptiles (Mafli et al 2011), birds (Roulin et al 2000;Scriba et al 2014), and mammals (Bubenik & Bubenik 1985;West & Packer 2002;Graipel et al 2014). Such behavioral differences might arise from pleiotropic effects of the alleles that determine melanic color.…”
Section: Discussionmentioning
confidence: 79%
“…), and mammals (Bubenik & Bubenik ; West & Packer ; Graipel et al. ). Such behavioral differences might arise from pleiotropic effects of the alleles that determine melanic color.…”
Section: Discussionmentioning
confidence: 99%